The Dominant Physical Factor Determines the Ability to Play Sepak Takraw in the Nilam Raya Team - Sari, Widdiana; Prawibowo, Muhammad (Program Pascasarjana Universitas Negeri Jakarta, 2025)
The study aimed to identify the physical condition factors that’s most influence the playing ability of sepak takraw athletes from the Nilam Raya team. Ten male athletes aged 15 to 20 were selected using a a purposive sampling technique, taking into account their active involvement in training and competitions. Data were collected through a series of tests covering leg muscle strength, body coordination, reaction speed, flexibility, and physical endurance. Furthermore, the athletes' technical abilities were measured through evaluations of their serving, passing, and smashing skills. The analysis revealed a strong correlation between body coordination and serving ability (r = 0.87), indicating that precise motor control is crucial for successful serving. Leg muscle strength significantly influenced the effectiveness of smashes (r = 0.84), which require explosive power and body stability. Meanwhile, reaction speed significantly correlated with passing accuracy (r = 0.81), demonstrating the importance of quick reflexes in responding to an opponent's play. These three physical components—coordination, leg muscle strength, and reaction speed—emerged as the dominant factors shaping sepak takraw athlete performance. These findings provide a scientific basis for coaches and sports practitioners to design more targeted and evidence-based training programs, focusing on developing physical aspects that have been shown to directly contribute to improving playing skills on the field.